PEDOT(PSS) as Solid Contact for Ion-Selective Electrodes: The Influence of the PEDOT(PSS) Film Thickness on the Equilibration Times - Guzinski, M.; Jarvis, J.; Perez, F.; Pendley, B.; Lindner, E.; De Marco, Roland; Crespo, G.; Acres, R.; Walker, R.; Bishop, J. (American Chemical Society, 2017)
To understand the rate determining processes during the equilibration of poly(3,4-ethylenedioxythiophene):polystyrenesulfonate-based (PEDOT(PSS)-based) solid contact (SC) ion-selective electrodes (ISEs), the surfaces of Pt, Au, and GC electrodes were coated with 0.1, 1.0, 2.0, and 4.0 µm thick galvanostatically deposited PEDOT(PSS) films. Next, potential vs time transients were recorded with these electrodes, with and without an additional potassium ion-selective membrane (ISM) coating, following their first contact with 0.1 M KCl solutions. The transients were significantly different when the multilayered sensor structures were assembled on Au or GC compared to Pt. The differences in the rate of equilibration were interpreted as a consequence of differences in the hydrophilicity of PEDOT(PSS) in contact with the substrate electrode surfaces based on X-ray photoelectron spectroscopy (XPS) and synchrotron radiation-XPS (SR-XPS) analysis of 10-100 nm thick PEDOT(PSS) films. The influence of the layer thickness of the electrochemically deposited PEDOT(PSS)-films on the hydrophilicity of these films has been documented by contact angle measurements over PEDOT(PSS)-coated Au, GC, and Pt electrode surfaces. This study demonstrates that it is possible to minimize the equilibration (conditioning) time of SC ISEs with aqueous solutions before usage by optimizing the thickness of the SC layer with a controlled ISM thickness. PEDOT(PSS)-coated Au and GC electrodes exhibit a significant negative potential drift during their equilibration in an aqueous solution. By coating the PEDOT(PSS) surface with an ISM, the negative potential drift is compensated by a positive potential drift related to the hydration of the ISM and activity changes at the PEDOT(PSS)|ISM interface. The potential drifts related to activity changes in the ISM have been determined by a novel adaptation of the "sandwich membrane" method.